2021
DOI: 10.1044/2021_jslhr-20-00661
|View full text |Cite
|
Sign up to set email alerts
|

Describing Vocalizations in Young Children: A Big Data Approach Through Citizen Science Annotation

Abstract: Purpose Recording young children's vocalizations through wearables is a promising method to assess language development. However, accurately and rapidly annotating these files remains challenging. Online crowdsourcing with the collaboration of citizen scientists could be a feasible solution. In this article, we assess the extent to which citizen scientists' annotations align with those gathered in the lab for recordings collected from young children. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Additionally, we note that real-world models with accuracies in the range of 0.60 have made real contributions to empirical research in child development. For example, measures of overheard speech derived from LENA’s speech classifier which has an overall weighted accuracy of 67% ( 79 ) have predicted various measures of language development in young children. A review paper provides a summary of works that used LENA’s in-built algorithms to detect aspects of the speech environment and were found to significantly predict individual differences in child language development as well as gold-standard laboratory measures ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we note that real-world models with accuracies in the range of 0.60 have made real contributions to empirical research in child development. For example, measures of overheard speech derived from LENA’s speech classifier which has an overall weighted accuracy of 67% ( 79 ) have predicted various measures of language development in young children. A review paper provides a summary of works that used LENA’s in-built algorithms to detect aspects of the speech environment and were found to significantly predict individual differences in child language development as well as gold-standard laboratory measures ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this also means that the audio recording is harder to process than an audio recording gathered in more manicured and stable conditions. Automatized algorithms attempt to classify child vocalizations into crying, laughing, canonical, and noncanonical, but precision is still a challenge (Schuller et al, 2019;Semenzin et al, 2021). We address the possibility that our vocalization counts confound actual speech and crying in several ways.…”
Section: Child Vocalizationsmentioning
confidence: 99%
“…Among a sample of either children younger than children in our sample (4-18 months) or slightly older children (11-53 months) but who were diagnosed with Angelman syndrome (a genetic disorder causing speech delays and intellectual disability), related research has shown that 72.89% of automatically identified segments were speech-like, 5.23% crying, and 1.65% laughing(Semenzin et al, 2021).…”
mentioning
confidence: 94%